A tool for quickly identifying gaps in diet of school children for nutritional educational interventions - Thomas V Chacko; Subhashini Ganesan (Wolters Kluwer Medknow Publications, 2018)
Compared to adults, assessment of dietary intake of school children has always been a great challenge in public health practice. Hence, this paper aims to share our experience in overcoming the problems in dietary assessment of large number of school children aged 6-17 years and the practicality of the tool for quickly identifying the broad gaps in the diet of individual Children for providing them dietary counseling. Based on the Indian Council of Medical Research/National Institute of Nutrition recommendations for balanced diet among school children, a simplified dietary gap assessment tool was developed to identify gross gaps in their diet and also a system of scoring it so as to measure effectiveness of the nutritional educational program. The simplified tool was effective in overcoming the challenge of making the children understand the concept of portion size by replacing it with inquiry of frequency of food intake in 'yes" or "no" terms and thereby making it easy to administer and is time efficient enough to enable a large number of students to be screened.